Development of Innovative Candied Chestnuts from Three Chestnut Cultivars Grown in Portugal - Foucher, Laure (2022)
The main purpose of this work is the development of a value-added product (candied chestnuts) from Portuguese chestnut (Castanea sativa) cultivars (Martainha, Longal and Judia), as a way to minimize product loss and wastes. To accomplish this goal, the effects of rehydration, cooking, and syrup conditions on composition, textural properties, and colour parameters of candied chestnuts were investigated. The obtained results revealed that the optimal conditions to prepare candied chestnuts with a sweet taste, dark brown colour, with a crispy texture on the outside and smooth texture in the inner flesh were rehydration at 45 °C for a period of 5 h, cooking in a pressure pan for 15 min, and an immersion process with sucrose syrup for two days (syrup with 25% of sucrose on the first day and syrup of 50% of sucrose on the second day). During the process, the drying loss, hydration ratio, and cooking gain of the different cultivars were about 90%, 79%, and 130%, respectively. The total colour difference of candied chestnuts ranged from 24.18 (Longal) to 29.95 (Judia), the stickiness was moderately intense, and the adhesiveness was high for the three varieties. Longal candied chestnuts were the softest and Martainha candied chestnuts were the hardest, the most elastic, and cohesive. Moreover, the candied chestnuts presented a moisture content ranging from 52.70% and 54.23%, amounts of carbohydrates in the range of 88.58 to 91.87 g/100 g d.m, values of protein (6.55–9.51 g/100 g d.m.), values of ash (0.78–1.98 g/100 g d.m.), and fat (0.87–1.58 g/100 g d.m.). In conclusion, the chestnuts of Portuguese cultivars Martainha, Longal and Judia reveal a good potential to produce candied products with high added value.